Synaptic, transcriptional and chromatin genes disrupted in autism - De Rubeis, Silvia; He, Xin; Goldberg, Arthur P.; Poultney, Christopher S.; Samocha, Kaitlin; Ercument Cicek, A.; Kou, Yan; Liu, Li; Fromer, Menachem; Walker, Susan; Singh, Tarjinder; Klei, Lambertus; et al. (Nature (London), 2014)
The genetic architecture of autism spectrum disorder involves the interplay of common and rare variants and their impact on hundreds of genes. Using exome sequencing, here we show that analysis of rare coding variation in 3,871 autism cases and 9,937 ancestry-matched or parental controls implicates 22 autosomal genes at a false discovery rate (FDR) < 0.05, plus a set of 107 autosomal genes strongly enriched for those likely to affect risk (FDR < 0.30). These 107 genes, which show unusual evolutionary constraint against mutations, incur de novo loss-of-function mutations in over 5% of autistic subjects. Many of the genes implicated encode proteins for synaptic formation, transcriptional regulation and chromatin-remodelling pathways. These include voltage-gated ion channels regulating the propagation of action potentials, pacemaking and excitability–transcription coupling, as well as histone-modifying enzymes and chromatin remodellers—most prominently those that mediate post-translational lysine methylation/demethylation modifications of histones. Whole-exome sequencing in a large autism study identifies over 100 autosomal genes that are likely to affect risk for the disorder; these genes, which show unusual evolutionary constraint against mutations, carry de novo loss-of-function mutations in over 5% of autistic subjects and many function in synaptic, transcriptional and chromatin-remodelling pathways. Autism-linked genetic factors analysed Autism spectrum disorder (ASD) is a broad group of brain development disorders, including autism, childhood disintegrative disorder and Asperger's syndrome, characterized by impaired social interaction and communication, repetitive behaviour and restricted interests. Two groups reporting in this issue of Nature have used large-scale whole-exome sequencing to examine the contribution of inherited and germline de novo mutations to ASD risk. Silvia De Rubeis et al . analysed DNA samples from 3,871 autism cases and 9,937 ancestry-matched or parental controls and identify more than 100 autosomal genes that are likely to affect risk for the disease. De novo loss-of-function mutations were detected in more than 5% of autistic subjects. Many of the associated gene products appear to function in synaptic, transcriptional, and chromatin remodelling pathways. Ivan Iossifov et al . sequenced exomes from more than 2,500 families, each with one child with ASD. They identify 27 high-confidence gene targets and estimate that 13% of de novo missense mutations and 43% of de novo 'likely gene-disrupting' (LGD) mutations contribute to 12% and 9% of diagnoses, respectively.